PWE-274 TACE or TAE for treatment of hepatocellular carcinoma?. (28th May 2012) - Meredith, P; Kohler, K; Jeffries-Chung, C; See, T-C; Griffiths, W J
Abstract : Introduction: Transarterial Chemoembolisation (TACE) and Transarterial Embolisation (TAE) are established treatments for Hepatocellular Carcinoma (HCC) though the superiority of TACE remains uncertain. The aim of this study was to evaluate and compare the efficacy of these modalities. Methods: Data for all patients undergoing a first course treatment of TACE or TAE at Addenbrooke's NHS Hospital over a 22-month period were retrospectively reviewed (n=41). All patients had radiologically and/or histologically diagnosed HCC. 23 patients underwent TACE until May 2010 and a change in policy, followed by 18 patients receiving TAE (there were no changes in selection criteria). 11 (27%) patients were bridged to liver transplantation, while 30 (73%) patients were palliative. Outcome measures included radiological response to "treatment" (1–3 TACE or TAE sessions), complications and survival. The fisher exact probability test and unpaired t-test were used for comparisons. Results: Five patients who did not undergo follow-up imaging were excluded. Overall a radiological response (partial or complete) was seen in 67% of patients. No significant difference was seen between TACE and TAE although there was a trend towards complete response in the TACE group (p=0.24) (Abstract PWE-274 table 1 ). Although number of lesions did not correlate with radiological response, a non-significant trend was seen in relation to size of largest lesion (median 41 mm with response vs median 33 mm with no response). No patient in the waiting list group developed clinical complications whereas 6 (20%) of the palliative group developed a significant infective complication (p=0.13). Complications appeared more common in those receiving TACE compared with TAE (25% vs 6%, p=0.15). Median survival in palliative patients was 15.1 months (6 deaths with TACE, 3 with TAE). In the waiting list group 8/11 received TAE and 10 have undergone transplant (median wait time 141 days), the remaining patient active 13 months since listing. Conclusion: This study has demonstrated reasonable efficacy of TAE for the treatment of HCC with minimal complications. There may be a trend towards more complete response with TACE though accompanied by increased complications. Both treatments appear similarly efficacious in prolonging survival which was favourable when compared with historical data. 1 TAE appeared effective in bridging patients to transplant and was well tolerated. Competing interests: None declared. Reference: 1. Llovet JM, Ricci S, Mazzaferro P, et al. Sorafenib in advanced hepatocellular carcinoma. N Engl J Med 2008;359 :378–90.